Possible use of calcifying nanoparticles in immature root apex treatment - Mohammed S Alenazy; Hezekiah A Mosadomi (Wolters Kluwer Medknow Publications, 2014)
Introduction: There are reports in the literature, which describe different techniques and materials in the challenging management of thin dentin walls and immature root apex. It has been suggested that calcifying nanoparticles (CNPs) could be used in the management of these conditions. The Hypothesis: Compositionally modified CNPs made into a paste could become efficacious in managing thin dentin walls and immature root apex. Calcium and phosphate ions when mixed with CNPs could form a synthetic nanopaste that clinicians could use to manage thin dentin walls and to get a biological seal for immature root apex. Evaluation of the Hypothesis: CNPs can replicate and could facilitate the aggregations of calcium hydroxyapatite to produce a self-surrounding shell. These characteristics of CNPs could be used through their biomineralization process as initial nidus of calcification for further calcification progression to achieve total biological apical seal. If the hypothesis could be supported by biomineralization behavior of the paste (CNPs, Ca2 + , and PO4− ), a new therapeutic agent would have been added to the armamentarium of endodontists. There is need for more in vivo and in vitro investigations of modified nanopaste to manage these conditions.